PERFECTION OF PRODUCTION TECHNOLOGY OF REBARS OF SMALL SECTIONS, ROLLED BY MULTISTRAND ROLLING-AND-SEPARATION - S. M. Zhuchkov; V. G. Razdobreev; P. V. Tokmanov; A. I. Leshchenko; M. I. Titov; A. V. Rusalenko (Литьë и металлургия)
The expediency of application no driving universal mills for increase o f a production efficiency bars of hire with use of no conventional process mac rolling of rolling-division is shown.